Cardiovascular diagnosis with frequency spectral analysis (FSA) and continuous wave doppler (CWD) - Merrill P. SPENCER (Archives of Acoustics)
This report reviews how the combined use of continuous wave Doppler ultrasound and frequency spectral analysis from the fast Fourier transform provides a useful means of finding and analysing non invasively a wide range of cardiovascular diagnostic information. Reliance is placed on the frequency resolution capability of CWD to follow increased velocities in arteries produced by arterial and cardiac value stenosis, valve regurgitations, congenital heart septal defects and arteriovenous shunts. The ability to detect turbulence energies simultaneously with high velocities "on line" with a video reproducable format improves and hastens the diagnosis. Quantitation of stenotic lesion is possible in terms of effective lumen diameter and pressure drop produced by the blood flow. Cardiac output and changes in stroke volume can also be computed.